Peran Mahasiswa dalam Menanamkan Nilai-Nilai Moderasi Beragama di Lingkungan Kampus - Susanti Susanti; Dewi Jayanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Indonesia is an archipelagic country whose people have a variety of cultures including differences in culture, religion, race, language, ethnicity, tradition, and so on. So addressing this requires tolerance in understanding all the differences that exist. Therefore, religious moderation is very appropriate to be used in the life of the nation and state, especially among students. Religious moderation is a middle way in dealing with differences in both extreme and fundamental groups. The role of students with their knowledge is expected to uphold the value of tolerance and as a pioneer in educating the public regarding religious moderation. Students are needed to socialize and develop religious moderation in society in order to create harmony and peace. Realizing religious moderation can be done by embracing each other and promoting the values of inter-religious tolerance. Religious moderation is the key to maintaining tolerance and harmony, both at the local, national and global levels. Rejecting extremism and liberalism in religion is the key to balance, for the maintenance of civilization and the creation of peace. In this way, each religious community can respect each other, accept differences, and live together in peace and harmony. This research was conducted because the spread of extreme, liberal, and intolerant notions only leads to the general public, but students and university students are also easy targets for their spread. This is because students who are relatively young are still in the stage of searching for identity, and students' low religious knowledge makes them easily influenced by these understandings. This research is a research with a qualitative approach. Data collection techniques using the method of observation, interviews, and documentation. From the results of the researcher's analysis, it was concluded that the efforts made in shaping the attitude of religious moderation of students on campus were by providing deep religious knowledge, being selective towards teaching staff, and accommodating to local culture. This is in accordance with the results of interviews and observations of researchers regarding the activities carried out.